PENGARUH ABSENSI TERHADAP NILAI AKHIR MATA KULIAH STATISTIK EKONOMI DAN BISNIS PADA MAHASISWA STIE H. AGUS SALIM BUKITTINGGI - Syavardie, Yimmi (jurnal ekonomi, 2014)
This study aims to determine: How big is the influence of attendance on the final valueof Economic and Business Statistics at STIEH. Agus Salim Bukittinggi. The samples were taken from all the students who took a course of economic and business statistics at least 265 people. For purposes of analysis, data were collected in though descriptive, validity, reliability, correlation and multiple regression. Descriptive analysis of the result sobtained that the data is normally spread, all variables arereliable as a research instrument. From the data processing obtaineda strong relationship between attendance at the final valueof Economic and Business Statistics at STIEH. Agus Salim Bukittinggi of 0.784. Moderate contribution to the final grade is attendance by 61.4% (the value of R²=0.614) so thatthe remaining38.6% is influencedbyother factorsoutside the model(other than the attendancefactor). There is asignificant relationship between attendance and final grades for r=0.784 and R2=0.614 and 0.001and 0.000 significant level of 5%. Normality test results, attendance data and the data for the final scores are normally distributed.